Thrombin Prevents the Expression of Inducible Nitric Oxide Synthase in Vascular Smooth Muscle Cells by a Proteolytically-Activated Thrombin Receptor - Schini-Kerth, Valérie B; Fißithaler, Beate; Andersen, Thomas T; Fenton, John W, II; Vanhoutte, Paul M; Busse, Rudi (Thrombosis and Haemostasis, 1995)
Proteolytically active forms of thrombin (α- and γ-thrombin) and thrombin receptor peptides inhibited the release of nitrite, a stable endproduct of nitric oxide, evoked by interleukin-1 β(IL-1 β) in cultured vascular smooth muscle cells while proteolytically inactive forms [D-Phe-Pro-Arg chloromethyl ketone-α-thrombin (PPACK-α- thrombin) and diisopropylphosphoryl-α-thrombin (DIP-α-thrombin)] had either no or only minimal inhibitory effects. Under bioassay conditions, perfusates from columns containing IL-1 β-activated vascular smooth muscle cells or cells treated with IL-1βplus PPACK-α-thrombin relaxed detector blood vessels. These relaxations were abolished by the inhibitor of nitric oxide synthesis, NG-nitro-L arginine. No relaxations were obtained with untreated cells or IL-1 β-treated cells in the presence of α-thrombin. The expression of inducible nitric oxide synthase mRNA and protein in vascular smooth muscle cells by IL-1 β was impaired by α-thrombin. These results demonstrate that thrombin regulates the expression of the inducible nitric oxide synthase at a transcriptional level via the proteolytic activation of the thrombin receptor in vascular smooth muscle cells